Managing (Fiscally) Resource Windfalls : Exploring Policy Options for the Democratic Republic of Congo - Pinto-Moreira, Emmanuel (World Bank, Washington, DC, 2016)
How should resource-dependent countries respond (fiscally) to resource price volatility? This note studies what determines revenue allocation between a "spend today" strategy and a "save now-spend tomorrow" approach in the context of the Democratic Republic of Congo. It uses a three-sector model in which public infrastructure investment has tangible benefits for private production and investment while also being subject to absorption constraints. The optimal allocation rule between spending today and asset accumulation is calibrated by minimizing a social loss function defined in terms of household welfare (measured by consumption volatility) and macroeconomic volatility (measured in terms of fiscal volatility only, or a composite measure involving real exchange rate volatility). The results indicate that, if properly managed, a sovereign fund could contribute significantly to macroeconomic stability in the Democratic Republic of Congo.